2018
DOI: 10.5194/amt-11-5941-2018
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen dioxide and formaldehyde measurements from the GEOstationary Coastal and Air Pollution Events (GEO-CAPE) Airborne Simulator over Houston, Texas

Abstract: The GEOstationary Coastal and Air Pollution Events (GEO-CAPE) Airborne Simulator (GCAS) was developed in support of NASA's decadal survey GEO-CAPE geostationary satellite mission. GCAS is an airborne pushbroom remote-sensing instrument, consisting of two channels which make hyperspectral measurements in the ultraviolet/visible (optimized for air quality observations) and the visible-near infrared (optimized for ocean color observations). The GCAS instrument participated in its first intensive field campaign du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
67
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 102 publications
(134 reference statements)
0
67
1
Order By: Relevance
“…In total, 15 Pandora direct sun instruments delivering at least 3 months of data have been considered here. They are listed in Table 3 with an indication of their location, ownership, availability (see also (Choi et al, 2019), the largest discrepancies being found in Texas (Nowlan et al, 2018). Good agreement of a few percent between Pandora and GeoTASO has been reported by Judd et al (2019), while differences increase when resampling the comparisons for larger simulated pixel sizes, up to about 40% bias for 10 18x18km², similar to the bias found with OMI (50%).…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…In total, 15 Pandora direct sun instruments delivering at least 3 months of data have been considered here. They are listed in Table 3 with an indication of their location, ownership, availability (see also (Choi et al, 2019), the largest discrepancies being found in Texas (Nowlan et al, 2018). Good agreement of a few percent between Pandora and GeoTASO has been reported by Judd et al (2019), while differences increase when resampling the comparisons for larger simulated pixel sizes, up to about 40% bias for 10 18x18km², similar to the bias found with OMI (50%).…”
mentioning
confidence: 58%
“…As already discussed in Section 5.1, for direct sun stations this could be related to issues with the determination of 5 stratospheric columns in the satellite algorithm. UHMT is a peculiar site, where several studies performed during the DISCOVER-AQ 2013 Texas campaign (Nowlan et al, 2018;Choi et al, 2019) suggested that those Pandora NO2 measurements tend to be too low. Finally, some sites (e.g.…”
mentioning
confidence: 99%
“…Elsewhere, Pandora data agree with aircraft measurements to within 20% on average, although much larger differences are observed for individual sites. A larger discrepancy for Pandora data in TX is also reported by Nowlan et al (2018), who used various NO 2 measurements to evaluate Geo-TASO NO 2 retrievals. Reasons for such exceptionally large differences could include strong gradients in the NO 2 field that are missed by aircraft spirals, errors in Pandora retrievals, or both.…”
Section: Comparison Between Pandora and Aircraft Observationsmentioning
confidence: 73%
“…A number of validation studies of space-based tropospheric NO 2 columns have been conducted using independent NO 2 observations from airborne in situ mixing ratio measurements (e.g., Boersma et al, 2008;Bucsela et al, 2008;Hains et al, 2010;Lamsal et al, 2014), ground-based total (e.g., Pandora instrument (Herman et al, 2009)) and tropospheric (e.g., MAX-DOAS instrument (e.g., Vlemmix et al, 2010;Irie et al, 2012)) column measurements, and airborne high-resolution DOAS measurements (Lamsal et al, 2017;Nowlan et al, 2018). Most validation studies utilizing in situ/ground-based observations have reported that satellite measurements tend to underestimate tropospheric NO 2 columns, especially over highly polluted areas (e.g., Hains et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…They combined ground-based and airborne measurements. DISCOVER-AQ involved the deployment of the Geostationary Trace gas and Aerosol Sensor Optimization instrument (GEOTASO, Leitch et al,2014;Nowlan et al,2016) and of the Geostationary Coastal and Air Pollution Events (GEO-CAPE) Airborne Simulator (GCAS, Kowalewski and Janz,2014;Nowlan et al,2018). In Europe, the two AROMAT campaigns, which took place in Romania in September 2014 and August 2015, demonstrated a suite of new instruments such as the Airborne imaging DOAS instrument for Measurements of Atmospheric Pollution (AirMAP, Schönhardt et al,2015;Meier et al,2017), the NO 2 sonde (Sluis et al, 2010), and the Small Whiskbroom Imager for atmospheric compositioN monitorinG (SWING, Merlaud et al,2018).…”
Section: Introductionmentioning
confidence: 99%